Functionally graded materials 1996 : proceedings of the 4th International Symposium on Functionally Graded Materials, AIST Tsukuba Research Center, Tsukuba, Japan, October 21-24, 1996 /: proceedings of the 4th International Symposium on Functionally Graded Materials, AIST Tsukuba Research Center, Tsukuba, Japan, October 21-24, 1996. (1997) - Unknown
No abstract available